2015
DOI: 10.1007/s00572-015-0647-2
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhiza affects nickel translocation and expression of ABC transporter and metallothionein genes in Festuca arundinacea

Abstract: Mycorrhizal fungi are key microorganisms for enhancing phytoremediation of soils contaminated with heavy metals. In this study, the effects of the arbuscular mycorrhizal fungus (AMF) Funneliformis mosseae (=Glomus mosseae) on physiological and molecular mechanisms involved in the nickel (Ni) tolerance of tall fescue (Festuca arundinacea = Schedonorus arundinaceus) were investigated. Nickel addition had a pronounced negative effect on tall fescue growth and photosynthetic pigment contents, as well as on AMF col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 54 publications
3
26
0
Order By: Relevance
“…Gerd. & Trappe under Ni exposure (Shabani et al, ) and NRAMP , MT2b , and PCS in Solanum lycopersicum L. inoculated with R. irregularis grown on HM‐polluted soil (Fuentes et al, ). These findings indicate that mycorrhizal‐induced transcriptional overexpression of host genes involved in HM transport, detoxification, and sequestration can lead to enhanced HM accumulation in mycorrhizal plants.…”
Section: Physiological and Molecular Mechanisms Of Hm Accumulation Inmentioning
confidence: 99%
“…Gerd. & Trappe under Ni exposure (Shabani et al, ) and NRAMP , MT2b , and PCS in Solanum lycopersicum L. inoculated with R. irregularis grown on HM‐polluted soil (Fuentes et al, ). These findings indicate that mycorrhizal‐induced transcriptional overexpression of host genes involved in HM transport, detoxification, and sequestration can lead to enhanced HM accumulation in mycorrhizal plants.…”
Section: Physiological and Molecular Mechanisms Of Hm Accumulation Inmentioning
confidence: 99%
“…Mycorrhizae may also alter host metabolism to respond to metal toxicity. Shabani et al (2016) have shown that inoculation of Festuca arundinacea with Funneliformis mosseae increased the transcription of host metallothioneins and ABC transporters (which aid in the excretion of toxins) in nickel-contaminated soil.…”
Section: Impact On Crop Healthmentioning
confidence: 99%
“…Similarly, presence of nickel in soil has been reported to have adverse effects on growth of tall fescue (Festuca arundinacea L.) and contents of photosynthetic pigments. Inoculation of these plants with AM fungi (R. mosseae) reduced nickel uptake from roots to shoots reflecting the importance of these fungi in relieving nickel stress (Shabani et al, 2016). Adverse effects of high concentration of zinc on the plant growth and other parameters, such as, putrescine profile in the leaves of poplar, have been reduced in plants colonized by Rhizophagus mosseae.…”
Section: Arbuscular Mycorrhizal Fungi and Phytoremediationmentioning
confidence: 99%